International Continence Society consensus on the diagnosis and treatment of nocturia. Issue 2 (19th February 2019) - Everaert, Karel; Hervé, Francois; Bosch, Ruud; Dmochowski, Roger; Drake, Marcus; Hashim, Hashim; Chapple, Christopher; Van Kerrebroeck, Philip; Mourad, Sherif; Abrams, Paul; Wein, Alan
Abstract: Introduction: Patients with nocturia have to face many hurdles before being diagnosed and treated properly. The aim of this paper is to: summarize the nocturia patient pathway, explore how nocturia is diagnosed and treated in the real world and use the Delphi method to develop a practical algorithm with a focus on what steps need to be taken before prescribing desmopressin. Methods: Evidence comes from existing guidelines (Google, PubMed), International Consultation on Incontinence‐Research Society (ICI‐RS) 2017, prescribing information and a Delphi panel (3 rounds). The International Continence Society initiated this study, the authors represent the ICI‐RS, European Association of Urology, and Society of Urodynamics, Female Pelvic Medicine and Urogenital Reconstruction (SUFU). Results: Diagnostic packages: consensus on, history taking for all causalities, intake diary (fluid, food) and bladder diary, not for its duration. Pelvic (women) or rectal (men) examination, prostate‐specific antigen, serum sodium check (SSC), renal function, endocrine screening: when judged necessary. Timing or empty stomach when SSC is not important. Therapeutic packages: the safe candidates for desmopressin can be phenotyped as no polydipsia, heart/kidney failure, severe leg edema or obstructive sleep apnea syndrome. Lifestyle interventions may be useful. Initiating desmopressin: risk management consensus on three clinical pictures. Follow‐up of desmopressin therapy: there was consensus on SSC day 3 to 7, and at 1 month. Stop therapy if SSC is <130 mmol/L regardless of symptoms. Stop if SSC is 130 to 135 mmol/L with symptoms of hyponatremia. Conclusion: A summary of the nocturia patient pathway across different medical specialists is useful in the visualization and phenotyping of patients for diagnosis and therapy. By summarizing basic knowledge of desmopressin, we aim to ease its initiation and shorten the patient journey for nocturia.